Access to chlamydia testing needed for high‐risk groups: patterns of testing and detection in an urban area of New Zealand - Sally B. Rose; Collette Bromhead; Beverley A. Lawton; Jane Zhang; James Stanley; Michael G. Baker (Elsevier, 2012)
Abstract Objective : To describe population rates of chlamydia testing and detection by sociodemographic characteristics, and to determine whether testing is reaching those groups most at risk of infection. Methods : Laboratory data for urogenital chlamydia tests in an urban region of New Zealand were collated for the period 1999 to 2005. Census data were used to estimate rates of testing and diagnosis (per 100,000 population). Regression analyses summarised patterns in testing and diagnosis by age, sex, ethnicity and socioeconomic deprivation (controlling for potential confounding factors). Results : Rates of chlamydia testing and detection differed significantly by age, sex, ethnicity and deprivation. Females had lower rates of chlamydia diagnoses than males (OR 0.4, 95% CI 0.39-0.42) but were tested five times more often. When tested, rates of chlamydia detection were significantly higher among Pacific (OR 2.33, 95% CI 2.16-2.5), and Māori (OR 2.01, 95% CI 1.87-2.17) than among European (reference group), and among individuals living in areas of greater socioeconomic deprivation (OR 1.66, 95% CI 1.55-1.77). Chlamydia diagnoses were significantly higher in the under 25 year old age group, with the highest odds of a positive result among the 15-19 year age group (OR 9.06, 95% CI 8.23-9.98). Conclusion : This analysis identified higher‐risk groups who appeared to be underserved by testing relative to their higher rates of infection (including Māori, Pacific, 15-19 year olds and individuals living in areas of high socioeconomic deprivation). Implications : Appropriate chlamydia control programs with testing targeted towards higher‐risk groups are urgently needed in NZ.